Bilateral suppurative parotitis in a neonate: a case report - Chordia, Srilakshmi M.; Arunagirinathan, Arulkumaran; Bhandary, Karthik S. (International Journal of Contemporary Pediatrics, 2019)
Acute suppurative parotitis is a very rare ailment to be encountered in the neonatal period. Here, we report a 13-day old hemodynamically stable neonate, who presented to us with bilateral tender, erythematous parotid swelling and purulent discharge exuding from stensen’s duct. He was exclusively breast fed and had no other risk factors. Provisional diagnosis of acute suppurative parotitis was made with clinical examination. On investigating, there was neutrophilic leukocytosis, elevated acute phase reactants, ultrasonogram showed hypoechoic areas and a heavy growth of Staphylococcus aureus was isolated on pus culture. Baby underwent incision and drainage on the day of admission and was started on appropriate parenteral antibiotics along with supportive management. There was a significant clinical response over next 24 hours. He was doing well throughout the hospital stay and antibiotic course was completed based on culture sensitivity pattern. He neither had any immediate complications during hospital stay nor developed any late complications on follow up. Prognosis of the condition is excellent with adequate timely management. Authors would like to report this case for its rarity and to emphasize on fact that though the condition is uncommon, acute neonatal parotitis should be included in the differentials of any unilateral or bilateral neonatal parotid swelling, as early diagnosis and prompt management of this entity is mandated for a favorable outcome and to limit complications drastically.